2002
DOI: 10.1093/humrep/17.4.1006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nuclear and cytoplasmic maturation in in-vitro matured human oocytes

Abstract: This work forms a basis for future studies aimed at optimizing nuclear and cytoplasmic maturation during in-vitro maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
150
4
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(179 citation statements)
references
References 62 publications
(82 reference statements)
16
150
4
3
Order By: Relevance
“…This stage may be particularly susceptible to damage; of relevance are studies performed in cat immature oocytes for which a pretreatment with a drug promoting chromatin compaction proved beneficial for subsequent developmental competence [42]. While we aimed to freeze oocytes during GV arrest, it is also possible that some of the oocytes began the process of spontaneous meiotic resumption in the time between follicle aspiration and freezing (about 2-4 h) [43]. If so, the oocytes may actually be undergoing germinal vesicle breakdown (GVBD), a time of considerable cellular remodeling, including microtubules that become more dynamic [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stage may be particularly susceptible to damage; of relevance are studies performed in cat immature oocytes for which a pretreatment with a drug promoting chromatin compaction proved beneficial for subsequent developmental competence [42]. While we aimed to freeze oocytes during GV arrest, it is also possible that some of the oocytes began the process of spontaneous meiotic resumption in the time between follicle aspiration and freezing (about 2-4 h) [43]. If so, the oocytes may actually be undergoing germinal vesicle breakdown (GVBD), a time of considerable cellular remodeling, including microtubules that become more dynamic [44].…”
Section: Discussionmentioning
confidence: 99%
“…Freezing during GVBD may thus be a particularly risky proposition, as supported in the bovine with improved outcomes when vitrifying M-II compared to GVBD oocytes [46]. Even if oocytes were true GVs at the time of cooling, it is relevant to note that in human GV, cytoplasmic microtubules are not acetylated [43], with acetylation of α-tubulin itself an indicator of heightened microtubule stability. This lack of microtubule acetylation could perhaps contribute to a particular sensitivity of GVs to cooling, with vitrification thus here again expected to minimize the negative effects of cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Studies including animal and human oocytes have shown that chromatin in GV oocytes of different final sizes is distinctly organized, which affects their maturation competence and later determines the course of embryo development (Combelles et al, 2002;Motlik & Fulka, 1976;Lefevre et al, 1989;Liu et al, 2006;Sun et al, 2004;Zuccotti et al, 1995). Chromatin remodeling includes morphologic changes such as condensation and de-condensation as well as functional changes such as transcription of particular chromatin regions.…”
Section: Chromatinmentioning
confidence: 99%
“…Those oocytes that have reached their final size and at the same time have the majority of chromatin configured in a circle around the nucleolus with some dense chromatin granules scattered across the nucleus, have optimum maturation capacity (Combelles et al, 2002).…”
Section: Chromatinmentioning
confidence: 99%
“…Cats serve as good models for addressing infertility syndromes in women, such as asynchronous oocyte cytoplasmic and nuclear maturation, ovarian hypersensitivity, and luteal dysfunction after gonadotropin therapy [6]. Interestingly, cat oocytes share several characteristics with human oocytes [7,8]: (1) the diameter of the oocyte proper and the germinal vesicle is equivalent (110 and 45 μm, respectively) in both species; (2) oocytes reach the metaphase II (MII) stage of meiosis after 24 h in culture; and (3) both species have a similar nuclear configuration with a small nucleolus and a fibrillar chromatin. In contrast, these morphological features are distinct or lacking in the typical laboratory mouse model.…”
Section: Introductionmentioning
confidence: 99%